Exploring stem cell biology in pituitary tumors and derived organoids. Issue 7 (17th June 2022) - Nys, Charlotte; Lee, Yu-Lun; Roose, Heleen; Mertens, Freya; De Pauw, Ellen; Kobayashi, Hiroto; Sciot, Raf; Bex, Marie; Versyck, Georges; De Vleeschouwer, Steven; Van Loon, Johannes; Laporte, Emma; et al.
Abstract : Pituitary tumorigenesis is highly prevalent and causes major endocrine disorders. Hardly anything is known on the behavior of the local stem cells in this pathology. Here, we explored the stem cells' biology in mouse and human pituitary tumors using transcriptomic, immunophenotyping and organoid approaches. In the prolactinoma-growing pituitary of dopamine receptor D2 knock-out mice, the stem cell population displays an activated state in terms of proliferative activity and distinct cytokine/chemokine phenotype. Organoids derived from the tumorous glands' stem cells recapitulated these aspects of the stem cells' activation nature. Upregulated cytokines, in particular interleukin-6, stimulated the stem cell-derived organoid development and growth process. In human pituitary tumors, cells typified by expression of stemness markers, in particular SOX2 and SOX9, were found present in a wide variety of clinical tumor types, also showing a pronounced proliferative status. Organoids efficiently developed from human tumor samples, displaying a stemness phenotype as well as tumor-specific expression fingerprints. Transcriptomic analysis revealed fading of cytokine pathways at organoid development and passaging, but their reactivation did not prove capable of rescuing early organoid expansion and passageability arrest. Taken together, our study revealed and underscored an activated phenotype of the pituitary-resident stem cells in tumorigenic glands and tumors. Our findings pave the way to defining the functional position of the local stem cells in pituitary tumor pathogenesis, at present barely known. Deeper insight can lead to more efficient and targeted clinical management, currently still not satisfactorily.